Neurophysiological effects of continuous cortical stimulation in epilepsy – Spike and spontaneous ECoG activity. Issue 1 (January 2019) - Westin, Karin; Lundstrom, Brian N.; Van Gompel, Jamie; Cooray, Gerald
Highlights: Stimulation over the seizure onset zone reduced background activity and interictal spike rate. Changes in power of background activity and spike rate showed a clear positive correlation. Possible causal relationship between spectral power, coherence and interictal spikes. Abstract: Objective: The effect of continuous subthreshold cortical stimulation (CSCS) over the seizure onset zone (SOZ) in epilepsy was analyzed to delineate the affected physiological processes. Method: ECoG data was recorded over SOZ and adjacent regions in patients (n = 7) with refractory-epilepsy. Data was reviewed before and during 2 Hz cortical electrical stimulation. Group differences were estimated using ANOVA and correlation with Pearson's r. Results: CSCS reduced background ECoG power at SOZ (p < 0.05), increased spectral coherence (p < 0.05) and reduced spike rate (p < 0.01) over all recorded sites. Spectral power and coherence (p < 0.01) correlated with spike rate at SOZ but not with each other at any location. Spike morphology correlated with spike-rate over all recorded sites (p < 0.0001) and with spectral power and coherence at SOZ (p < 0.01). Conclusion: This study shows changes in cortical electrophysiology during CSCS over the SOZ where spike rate reduction correlated with two independent electrophysiological parameters, background power and coherence. These results suggest the possibility of a causal relationship between spectral power, coherence and interictal spikes which may be related to seizure rate. Significance: Improved understanding of the effect of electrical stimulation on epileptic tissue could suggest improvements in stimulation paradigms to reduce seizure frequency.